Collaboration, consultation, and teamwork for students with special needs - Dettmer, Peggy; Knackendoffell, Ann;Thurston, Linda P. (Upper Saddle River, New Jersey : Pearson Education, 2013)
The seventh edition ofCollaboration, Consultation, and Teamwork for Students with Special Needs,focuses on collaboration in a variety of environments and emphasizes constructive ways to use educator differences to serve students with special needs. This text$1 (Bs broad perspective ensures coverage of the history of collaboration, ways to structure and implement collaborative teams, important processes and practices that ensure effective co-educator partnerships, and the external support that makes collaborative school consultation successful. The seventh edition features new chapters devoted to professional perspectives, personal preferences, paraeducators and evaluation techniques. With expanded Technology Tools sections, coverage of the latest educational reforms, and updated activities, this edition prepares educators, school personnel, families, and community leaders with a strong knowledge base that celebrates the strengths in personal differences.s
Part 1. Contexts for working together as co-educators -- 1. Working together in collaboration, consultation and teams -- 2. Working together with professional perspectives that differ -- 3. Working together with personal preferences that differ -- Part 2. Content for working together as co-educators -- 4. Components, structures and methods for collaboration, consultation, and teamwork -- 5. Problem-solving strategies for collaborative school consultation and teamwork -- 6. Organization and management of collaborative school consultation -- Part 3. Processes for working together as co-educators -- 7. Communicating as collaborators, consultants and team members -- 8. Cultivating home-school collaborations and partnerships -- 9. Working together for students in diverse populations -- Part 4: Practices for working together as co-educators -- 10. Collaborating and co-teaching for students with special needs -- 11. Supervising and collaborating with paraeducators -- 12. Evaluation of collaborative school consultation -- Part 5. Support for working together as co-educators -- 13. Developing and utilizing collaborations with educational personnel and community organizations -- 14. Leadership, mentorships, and professional development for collaborative school consultation -- 15. Synthesis and support for working together as co-educators.
Includes bibliographical references and index.
Keywords: TEACHING TEAMS